Intracellular pH and the control of multidrug resistance. - Simon, S (1994)
Many anticancer drugs are classified as either weak bases or molecules whose binding to cellular structures is pH dependent. Accumulation of these drugs within tumor cells should be affected by transmembrane pH gradients. Indeed, development of multidrug resistance (MDR) in tumor cells has been correlated with an alkaline shift of cytosolic pH. To examine the role of pH in drug partitioning, the distribution of two drugs, doxorubicin and daunomycin, was monitored in fibroblasts and myeloma cells. In both cell types the drugs rapidly accumulated within the cells. The highest concentrations were measured in the most acidic compartments--e.g., lysosomes. Modifying the cellular pH in drug-sensitive cells to mimic reported shifts in MDR caused an immediate change in the cellular drug concentration. Drug accumulation was enhanced by acidic shifts and reversed by alkaline shifts. All of these effects were rapid and reversible. These results demonstrate that the alkaline shift observed in MDR is sufficient to prevent the accumulation of chemotherapeutic drugs independent of active drug efflux.